What would you like to do?

# 1 factorial is equal to 1?

# 1 milliliter equals 1 what?

1 milliliter equals one cubic centimeter.

# What is the rationale for defining 0 factorial to be 1?

What is the rationale for defining 0 factorial to be 1? Answer The defining 0 factorial to be 1 is not a rationale. "Why is zero factorial equal to one?" is …a problem that one has to prove. When 0 factorial to be 1 to be proved, the defining 0 factorial to be 1 is unvaluable. One has only one general primitive definition of a factorial number: n! = n x (n-1) x (n-2) x (n-3) x ... x 2 x 1. After that zero factorial denoted 0! is a problem that one has to accept by convention 0!=1 as a part of definition. One has to prove zero factorial to be one. Only from the definition of a factorial number and by dividing both sides by n one has: n!/n (n-1)! or (n-1)! = n!/n when n=2 one has (2-1)! = 2!/2 or 1! = 2x1/2 or 1! = 1 when n=1 one has (1-1)! = 1!/1 or 0! = 1/1 or 0! = 1. = This is a proof that zero factorial is equal to one to be known. But a new proof is: A Schema Proof Without Words That Zero Factorial Is Equal To One. n! = ...Explanation of n!... ... ... ... 6! = 720 = 1×76 -6×66 +15×56 -20×46 +15×36 -6×26 +1×16 5! = 120 = 1×65 -5×55 +10×45 -10×35 + 5×25 -1×15 4! = ..24 = 1×54 -4×44 + 6×34 - 4×24 + 1×14 3! = ....6 = 1×43 -3×33 + 3×23 - 1×13 2! = ....2 = 1×32 -2×22 + 1×12 1! = ....1 = 1×21 -1×11 0! = ...... = 1×10 ........... 0! = 1×10 = 1×1 = 1 Conclusion 0! = 1 Now the expression 0! = 1 is already a proof, not need a definition nor a convention. So the defining 0 factorial to be 1 is unvaluable. The proof "without words" above that zero factorial is equal to one is a New that: *One has not to accept by convention 0!=1 anymore. *Zero factorial is not an empty product. *This Schema leads to a Law of Factorial. Note that the above schema is true but should not be used in a formal proof for 0!=1. The problem arises when you simplify the pattern formed by this schema into a MacLauren Series, which is the mathematical basis for it in the first place. Upon doing so you arrive with, . This representation illustrates that upon solving it you use 0!. In proofs you cannot define something by using that which you are defining in the definition. (ie) 0! can't be used when solving a problem within a proof of 0!. For clarification, the above series will represent the drawn out solution for the factorial of a number, i. (ie) 1×76 -6×66 +15×56 -20×46 +15×36 -6×26 +1×16 , where i=6.

# What does 1 1 equal?

1+1= a window 1+1=2

# Is 1 liter equal to 1 quart?

No, they are different systems. 1 litre is 1.0567 US quart.

# How do you cut stumps in Rune Factory 1?

You have to use an axe to chop stumps in Rune Factory

# How do you get married in Rune Factory 1?

You finish the requirements for the specific person you want to marry and then you have to talk to her at a certain time and place for the proposal option to arrive.

# How much equal to 1 and 1?

it may be 1 or 2 or 11 .as you do not clear your quest en

# What is 1 factorial?

1 factorial = 1

# How is 1 plus 1 equals 5?

It can't

# Does 1 liter equals 1 quart?

they are about the same

Answered

# Is 1 6 equal to 1 3?

2 sixths are equal to 1 third

Answered

# How do you get a hammer on Rune Factory 1?

buy one from the place you get weapons

Answered

In Plumbing

# Does 1 cfh equals 1 psi?

No. CFH is a capacity rating of pipe (natural gas), representing Cubic Feet per Hour. PSI is a pressure unit: Pounds(force) per Square Inch. The pressure will affect how fast …the gas flows.

Answered

In Algebra

# How can you Prove that e equals the infinite sum of 1 divided by x factorial?

This is actually quite easy to prove. The Taylor series of the exponential function, e^x (using "^" for power) is 1 + x^1/1! + x^2/2! + x^3/3! + x^4/4! ..., so all you need to… do is replace the exponent "x" by 1. (To be precise, you would also have to prove that the corresponding Taylor series is correct - that means proving that the residual tends towards zero. This is the case for most commonly used functions, but it must still be proven for individual cases such as this one.)

Answered

In Science

# How does 1 1 1 1 equal 5?

One way is to use the factorial sign (1+1+1)! - 1 = (3!) - 1 = 6-1 = 5